REIMAGINING LANGUAGE LEARNING THROUGH ARTIFICIAL INTELLIGENCE AND GAMIFICATION FOR GLOBALLY MOBILE LEARNERS IN NON-IMMERSIVE CONTEXTS (WITH A FOCUS ON DAZ/DAF): Received: 12th August 2025, Revised: 11th September 2025, Accepted: 17th October 2025, Date of Publication: 06th November 2025 - Dorcas O. Ezekiel,; Ezekiel Olagunju, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This article advances a critical reimagining of German language acquisition for globally mobile learners navigating non-immersive, digitally mediated contexts. Positioned at the intersection of Second Language Acquisition (SLA), cognitive linguistics, and human-computer interaction, the study interrogates the structural and pedagogical limitations of current Mobile-Assisted Language Learning (MALL) platforms—particularly their failure to support integrated, skill-balanced development in linguistically demanding contexts such as DaZ/DaF. Drawing on Design-Based Research (DBR), the authors propose a multi-tiered mobile learning ecology anchored in a prototypical application that combines AI-driven adaptivity with narrative-based gamification. This hybrid architecture simulates immersive conditions through city-based tasks, interactive dialogue flows, and CEFR-aligned communicative scenarios. Empirical findings from a purposively sampled cohort of fifty globally mobile learners reveal persistent cognitive and affective challenges, including fragmented input, insufficient feedback, and metacognitive disorientation. The prototype responds by embedding linguistic scaffolding, affect-sensitive interaction design, and dynamic personalization mechanisms to bridge the gap between learner autonomy and structured progression. By repositioning non-immersed learners as central actors in the design of pedagogically rigorous, technologically augmented language learning environments, this study articulates a scalable and theoretically grounded framework for post-immersion language pedagogy. In so doing, it offers a substantive contribution to ongoing debates in SLA, educational technology, and transnational language instruction—proposing not merely an app, but a paradigm shift in how language acquisition is imagined and operationalized in the 21st century.